Entomological aspects of Chagas' disease transmission in the domestic habitat, Argentina - Catala, Silvia Susana (2004)
Objective. To study the risk of Trypanosoma cruzi domestic transmission using an entomological index and to explore its relationship with household's characteristics and cultural aspects. Methods. There were studied 158 households in an endemic area in Argentina. Each household was classified according to an entomological risk indicator (number of risky bites/human). A questionnaire was administered to evaluate risk factors among householders. Results. Infested households showed a wide range of risk values (0 to 5 risky bites/human) with skewed distribution, a high frequency of lower values and few very high risk households. Of all collected Triatoma infestans, 44% had had human blood meals whereas 27% had had dogs or chickens blood meals. Having dogs and birds sharing room with humans increased the risk values. Tidy clean households had contributed significantly to lower risk values as a result of low vector density. The infested households showed a 24.3% correlation between time after insecticide application and the number of vectors. But there was no correlation between the time after insecticide application and T. infestans' infectivity. The statistical analysis showed a high correlation between current values of the entomological risk indicator and Trypanosoma cruzi seroprevalence in children. Conclusions. The risk of T. cruzi domestic transmission assessed using an entomological index show a correlation with children seroprevalence for Chagas' disease and householders' habits.